Alleviation of renal injury in rabbits by allisartan. (February 2023) - Li, Ruibin; Li, Li; Zhang, Jidong; Wang, Dong; Cui, Xiaoran; Bai, Long; Zhao, Lei; Yang, Xiaohong
The objective of this study was to determine the relationship between renal injury and inflammatory response induced by high-fat diet in rabbits and the interventional effect of allisartan. Fifteen 6-week-old healthy male rabbits were randomly divided into three groups: normal control (NC) group, high-lipid diet (HLD) group, high-lipid diet and allisartan (HLD+ALST) group. After allisartan treatment for 12 weeks, changes in total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), serum creatinine (Scr) and blood urea nitrogen (BUN) were measured enzymatically in the three groups. The left side of the kidney tissue was kept for paraffin section, and HE staining, periodic acid-Schiff (PAS) staining and Masson staining were used to observe the renal pathologic changes. TC, TG, LDL-C, Scr and BUN levels were all higher and HDL-C levels were lower in the HLD group compared with the NC group. Compared with the HLD group, Scr and BUN levels were significantly decreased in the HLD+ALST group. The results of HE staining showed that allisartan improved the changes of renal tissue morphology in rabbits on high-fat diet, reduced glomerular mesangial cell proliferation and improved glomerulosclerosis; PAS staining showed that glomerular glycogen deposition was reduced and glomerular red staining was significantly lighter; Masson staining showed that renal tubular blue-stained collagen fibers were reduced. In conclusion, hyperlipidemia can lead to aberrant expression of multiple cellular proteins and kidney tissue morphological damage in rabbits. On the other hand, allisartan attenuated renal injury and the mechanism may be related to the downregulation of the inflammatory response.